The challenges of everyday technology in the workplace for persons with acquired brain injury. (July 2012) - Kassberg, Ann-Charlotte; Prellwitz, Maria; Larsson Lund, Maria
Abstract Purpose: To explore and describe how persons with an acquired brain injury (ABI) managed the everyday technology (ET) that they needed to use in their workplace and how this use influences their opportunities to work. Methods: Nine persons with an ABI were interviewed and observed when managing ET in their workplace. The data were analysed qualitatively with a constant comparative method. Results: The main category, "The challenge of managing ET in the workplace", consisted of three categories, all of which reflected different kinds of discrepancies between the participants' ability to manage ET and the demands that ET imposes on them in work: "Struggling with ET to be able to continue to work; "Depending on strategies to cope with ET to continue in a particular profession", and "Managing ET at work but concerned about keeping up with the changes". Conclusions: The result revealed discrepancies between the abilities of the persons with ABI to manage ET in relation to the demands that technology imposed on them in their work setting. This indicated that professionals need to consider the role of ET when designing interventions supporting a person's return to work after an ABI.